2021
DOI: 10.1098/rspb.2021.0803
|View full text |Cite
|
Sign up to set email alerts
|

Genomic regions associated with adaptation to predation in Daphnia often include members of expanded gene families

Abstract: Predation has been a major driver of the evolution of prey species, which consequently develop antipredator adaptations. However, little is known about the genetic basis underpinning the adaptation of prey to intensive predation. Here, we describe a high-quality chromosome-level genome assembly (approx. 145 Mb, scaffold N50 11.45 Mb) of Daphnia mitsukuri , a primary forage for many fish species. Transcriptional profiling of D. mitsukuri exposed to fish kairomone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 71 publications
(85 reference statements)
1
20
0
Order By: Relevance
“…Higher temperatures can serve as a proxy for shallower depths, and therefore more incoming radiation. This may explain why our dataset shows enrichment of phototransduction genes as a response to temperature while previous studies have observed phototransduction gene enrichment in response to kairomones [31].…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Higher temperatures can serve as a proxy for shallower depths, and therefore more incoming radiation. This may explain why our dataset shows enrichment of phototransduction genes as a response to temperature while previous studies have observed phototransduction gene enrichment in response to kairomones [31].…”
Section: Discussionmentioning
confidence: 67%
“…This study and Tams et al explicitly avoided the addition of conspecific alarm cues in our kairomone mixture as to measure only the effect of predator odors [73]. Other studies, such as [30, 31], tested responses to a mixture of predator-specific odors and alarm cues released by consumed conspecifics. Mitchell et al call for the separation of nomenclature between cues released from the predator regardless of diet and diet-specific cues [32], so that researchers can more accurately discern the independent effects of these different kairomone compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O . mykiss were fed TetraMin Tropical Flakes (Tetra, Blacksburg, Virginia, USA) prior to kairomone collection, rather than juvenile conspecific daphniids as in some other studies [ 27 , 28 ]. We selected this method to minimize the presence of conspecific alarm cues in the isolated kairomone media, so that we could measure the phenotypic and genetic responses to only predator-released, diet agnostic kairomone cues.…”
Section: Methodsmentioning
confidence: 99%
“…This type of rapid gene evolution is particularly common in gene families involved in arms races such as immune genes (Machado & Ottolini, 2015; Malmstrøm et al, 2016). However, other types of ecologically relevant adaptation have been shown to follow this pattern of rapid changes in copy number such as expansions in hypoxia‐related genes in high‐altitude yaks (Qiu et al, 2012) and chemoreception and vision genes for predator responses in Daphnia (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%